All Days 2008
DOI: 10.2118/115679-ms
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Oil Recovery From Siliceous Shale by CO2 Injection

Abstract: Enhanced oil recovery from fractured low permeability reservoir rock is challenging and while studied previously, significant challenges remain in improving the recovery factor. In many cases the reservoir has been pressure depleted and gas released from solution. In such cases, continuous gas pathways from fracture to the matrix may have been created aiding our ability to deliver gas to the matrix. Gas injection (i.e., CO2) then proceeds from immiscible to perhaps miscible conditions. The efficiency of gas tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…Although the oil recovery from a tighter Lower Bakken sample was much lower than the Middle Bakken samples, the recovery was surprisingly high because of very low permeability of the source shale. Kovscek et al (2008) did countercurrent flow (flow across one face of the core) and concurrent flow (flow along the length of the core) experiments to investigate oil recovery from siliceous shale (0.02-1.3 mD) by CO 2 injection. They observed that the oil recovery was aided by the presence of continuous gas pathways from fracture to matrix that may help CO 2 penetrate into the matrix.…”
Section: Experimental Results On Huff and Puff Gas Injectionmentioning
confidence: 99%
“…Although the oil recovery from a tighter Lower Bakken sample was much lower than the Middle Bakken samples, the recovery was surprisingly high because of very low permeability of the source shale. Kovscek et al (2008) did countercurrent flow (flow across one face of the core) and concurrent flow (flow along the length of the core) experiments to investigate oil recovery from siliceous shale (0.02-1.3 mD) by CO 2 injection. They observed that the oil recovery was aided by the presence of continuous gas pathways from fracture to matrix that may help CO 2 penetrate into the matrix.…”
Section: Experimental Results On Huff and Puff Gas Injectionmentioning
confidence: 99%
“…The CT scan method is considered to be a nondestructive method to measure the cores' porosity, gas or oil saturation, and lithology characteristics within the cores (Siddiqui and Khamees, 2004;. The CT scan method has been widely used in petroleum engineering applications for describing the core porosity (Siddiqui et al, 2005), relative permeability (MacAllister et al, 1993), investigating the performance during core flooding experiments (London, et al, 2014), or other EOR processes (Kovscek et al, 2008;Simjoo et al, 2013;Tovar et al, 2014;. For this study, core plugs were scanned during the huff-n-puff tests to reflect the gas or oil saturation changes inside the core, and to help calculate the oil recovery in different stages.…”
Section: Introductionmentioning
confidence: 99%
“…Chapter provides a brief introduction and background to Unconventional (Hawthorne et al, 2013;Yu et al, 2018;Kovscek et al, 2008;USGS, 2013;Sheng and Chen, 2014;Sheng, 2015, Sun et al, 2016Tovar et al, 2014). That being said, not many major successful EOR programs have been documented (Hoffman and Evans, 2016).…”
Section: Synopsismentioning
confidence: 99%